Evaluation of sperm quality in male rats treated with Sauropus androgynus (L.) merr. leaf fractions - Ni Putu Ermi Hikmawanti; Numlil Khaira Rusdi; Silvy Yulida (Universitas Ahmad Dahlan, 2020)
Sauropus androgynus (L.) Merr. or katuk is one of the medicinal plants broadly used in Indonesia as it has active compounds that can, among others, stimulate reproductive hormones. This study was aimed to determine which active fraction of S. androgynus leaves that have the potential to improve the sperm quality of male rats based on three parameters, namely sperm count, viability, and motility. It employed fractionation using the liquid-liquid technique with n-hexane, ethyl acetate, and water solvents to obtain the fractions. Twenty-four mature Sprague-Dawley male rats were divided into four equal groups: the normal group (untreated group) received 0.5% Na-CMC suspense, and the three fraction groups were given the n-hexane, ethyl acetate, and water fraction p.o., respectively, at the dose of 11.85 mg.Kg-1 BW daily for seven days. Sperm count, viability, and motility were measured on Day 8 (after treatment) from the sperm samples collected at the cauda epididymis of the sacrificed test rats. The results showed that compared with the normal group, the n-hexane and ethyl acetate fractions significantly increased the three parameters (p<0.05). Therefore, the S. androgynus leaf fractions have the potential as a natural material that can increase the fertility of male rats.Â